Disaster averted: Community resilience in the face of a catastrophic flood. Issue 3 (2nd July 2016) - O'Neill, H. Katherine; McLean, Andrew J.; Kalis, Renetta; Shultz, James M.
ABSTRACT: In the spring of 2009, the Fargo, North Dakota, metropolitan area had 5 days to lay millions of sandbags to avoid devastation from record flooding of the Red River of the North. The community was able to successfully mitigate the flooding and escape potentially catastrophic economic, physical, and mental health consequences. We hypothesized that Fargo flood protection efforts reflected the community resilience factors proposed by Norris, Stevens, Pfefferbaum, et al. (2008): citizen involvement in mitigation efforts, effective organizational linkages, ongoing psychosocial support, and strong civic leadership in the face of rapidly changing circumstances. This community case report utilizes an extensive review of available sources, including news reports, government documents, research articles, and personal communication. Results demonstrate that Fargo's response to the threat of catastrophic flooding was consistent with Norris et al.'s (2008) factors of community resilience. Furthermore, success in 2009 carried over into future flood prevention and response efforts, as well as a structured approach to building psychological resilience. This case study contributes to the literature on community resilience by describing a community's successful efforts to avert a potentially catastrophic disaster.